Edukasi Kader Tuberkulosis dalam Penemuan Kasus Tuberkulosis dengan Pendeketan Theory of Planned Behavior - Fitriyani, Lia; Cholifatul Izza, Nurril; Purwadi, Hendro; Aulia Putri, Natasya Rizky (LPPM Akbid Harapan Ibu Pekalongan, 2025)
Indonesia has the third highest number of tuberculosis cases in the world after India and China. The most cases of tuberculosis occur in West Java, which is 73%. In 2021, there were 3,962 cases of tuberculosis in Depok City. TB case detection behavior is predictable, and the intent, purpose, and intent to carry out TB case detection are influenced by attitudes towards these behaviors, subjective norms, and perceived behavioral control (PBC). This community service activity was carried out in Depok City. This activity will be carried out for two months from April to May 2024. The number of participants in this activity was 30 people. The stages of this activity include preparation, implementation, monitoring, and evaluation. The results of this study show that education based on Theory of Planned Behavior (TPB) changes executive knowledge and behavior to be effective in detecting tuberculosis cases.